Audit Sistem Informasi Penerimaan Mahasiswa Baru STIMIK Kaputama Menggunakan Framework Cobit 5 - Alfina Damayanti; Armadani Simanjorang; Ayu Syahfitri; Bayu Juliansyah (Modem : Jurnal Informatika dan Sains Teknologi., 2024)
Abstract: The New Student Admission Information System (SIPMB) at STMIK Kaputama aims to enhance efficiency and transparency in the student admission process. This study conducted an information system audit using the COBIT 5 framework to evaluate system maturity and provide improvement recommendations. The audit results indicate that the system has not met the expected targets in all domains, with an average maturity level of 1.35 or 135%, classified as Fully Achieved (F). However, according to the capability model mapping condition index, the value is at level 1 (Performed Process). STMIK Kaputama needs to increase openness to innovation inputs and clear communication with prospective students to avoid errors in the admission process, as well as improve service quality for prospective students.